Reference genome of the nutrition-rich orphan crop chia (Salvia hispanica) and its implications for future breeding - Gupta, Parul; Geniza, Matthew; Elser, Justin; Al-Bader, Noor; Baschieri, Rachel; Phillips, Jeremy Levi; Haq, Ebaad; Preece, Justin; Naithani, Sushma; Jaiswal, Pankaj (Frontiers in Plant Science, 2023)
Chia (Salvia hispanica L.) is one of the most popular nutrition-rich foods and pseudocereal crops of the family Lamiaceae. Chia seeds are a rich source of proteins, polyunsaturated fatty acids (PUFAs), dietary fibers, and antioxidants. In this study, we present the assembly of the chia reference genome, which spans 303.6 Mb and encodes 48,090 annotated protein-coding genes. Our analysis revealed that ~42% of the chia genome harbors repetitive content, while we identified ~3 million single nucleotide polymorphisms (SNPs) and 15,380 simple sequence repeat (SSR) markers. By investigating the chia transcriptome, we have discovered that ~44% of the genes undergo alternative splicing with a higher frequency of intron retention events. Additionally, we identified chia genes associated with important nutrient content and quality traits, such as the biosynthesis of PUFAs and seed mucilage fiber (dietary fiber) polysaccharides. Notably, this is the first report of in-silico annotation of a plant genome for protein-derived small bioactive peptides (biopeptides) associated with improving human health.To facilitate further research and translational applications of this valuable orphan crop, we have developed the Salvia genomics database (SalviaGDB), accessible at https://salviagdb.org.